2014
DOI: 10.1063/1.4905454
|View full text |Cite
|
Sign up to set email alerts
|

Optical temperature sensing by upconversion luminescence of Er doped Bi5TiNbWO15ferroelectric materials

Abstract: The Er3+ doped Bi5TiNbWO15 ceramics have been synthesized using conventional solid-state reaction techniques. The crystal structure, ferroelectric properties, UC emission properties and especially the temperature sensing behaviors were systematically studied. With increasing Er3+ content, the investigation of XRD pattern, the ferroelectric loop and the UC emission indicated that the Er3+ ions dopants preferentially substituted the A sites of Bi3TiNbO9 and then Bi2WO6. Based on fluorescence intensity ratio (FIR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 36 publications
(31 reference statements)
0
15
0
Order By: Relevance
“…For comparison, the theoretical maximum value S R and corresponding temperature for other Er 3+ -doped materials in the literature, which include oxides, fluorides and glasses, are also shown in Table I. [24][25][26][27][28] Here, the maximum S R (0.0037 K À1 ) is obtained for KNNE ceramics, which is similar to other Er 3+ -doped materials. Thus, it can be concluded that the KNNE ceramics have great potential for the development of temperature sensors.…”
Section: Resultsmentioning
confidence: 98%
“…For comparison, the theoretical maximum value S R and corresponding temperature for other Er 3+ -doped materials in the literature, which include oxides, fluorides and glasses, are also shown in Table I. [24][25][26][27][28] Here, the maximum S R (0.0037 K À1 ) is obtained for KNNE ceramics, which is similar to other Er 3+ -doped materials. Thus, it can be concluded that the KNNE ceramics have great potential for the development of temperature sensors.…”
Section: Resultsmentioning
confidence: 98%
“…The results in the study indicate that the waveguiding performance of microfibers is quite similar to that reported previously. 29,30 …”
Section: Resultsmentioning
confidence: 99%
“…The results in the study indicate that the waveguiding performance of microbers is quite similar to that reported previously. 29,30 Fig. 6 Lifetime decay curves of b-NaGdF 4 :Yb 3+ /Tm 3+ thin films with and without silver.…”
Section: Transmission Loss Of Ag and Without Ag-doped Microbersmentioning
confidence: 99%
“…Recently, tungstate materials have fascinated huge curiosity for luminescence applications because of the strong and broad absorption band of the W–O bond and its chemical and thermal stability. Owing to this, the tungstate materials including CdWO 4 , CaWO 4 , and KGd­(WO 4 ) 2 can be used for various applications in the fields of scintillators, phosphors, and laser materials. However, there is a lack of proper research work reported on the luminescent thermometric characteristics of tungstate-based phosphors. Therefore, in this paper, a new Er 3+ /Yb 3+ -codoped phosphor based on the GdBiW 2 O 9 host was successfully developed via a solid-state approach, and the structure and UC characteristics were investigated.…”
Section: Introductionmentioning
confidence: 99%